The influence of quality characteristics of aquatic products on its price determination in China-A case of salmon products in supermarkets of Shanghai - Ya Du (Aquaculture and Fisheries, 2020)
The relationship between salmon prices and attributes were explored using the samples collected in supermarkets in Shanghai, China. The results showed that the price of the salmon did not have a significant relationship with the depth of orange color of salmon, unlike the results of stated preferences of western consumers in the previous studies. Whereas, smoked products had a positive relationship with price in the linear model form, and as the main importing country, Norway has the strongest positive relationship with price. In China salmon demand is expected to increase in future, salmon attributes highly appreciated in the market are different from western countries and salmon exporters need to recognize China as a special market for effective market.